1990
DOI: 10.1152/ajpendo.1990.259.6.e787
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and ontogeny of thyrotropin-releasing hormone degrading enzymes in rats

Abstract: The distribution and ontogeny of tissue prolyl endopeptidase and pyroglutamyl peptidase I activities were studied in the rat from the 7th day before birth to adulthood. While low levels of prolyl endopeptidase activity were demonstrable in many fetal tissues, activity in brain cortex, hypothalamus, lung, and kidney increased dramatically during the 2 wk after birth, gradually returning to adult levels. In adult rats, levels of tissue prolyl endopeptidase activity were highest in kidney, when compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 28 publications
6
39
2
Order By: Relevance
“…Caspase-6 is involved in apoptosis by the degradation of poly(ADP-ribose) polymerase and DNA topoisomerase I (15). Recently, it has been shown that caspase-6 and prolyloligopeptidase participate in the processing of amyloid precursor protein (13,16,17). In addition, inhibitors of prolyloligopeptidase have been reported to enhance cognition and are being explored for the treatment of Alzheimer's disease (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…Caspase-6 is involved in apoptosis by the degradation of poly(ADP-ribose) polymerase and DNA topoisomerase I (15). Recently, it has been shown that caspase-6 and prolyloligopeptidase participate in the processing of amyloid precursor protein (13,16,17). In addition, inhibitors of prolyloligopeptidase have been reported to enhance cognition and are being explored for the treatment of Alzheimer's disease (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…1). This appears to be inconsistent with several studies reporting that the brain contained higher POP activity than other tissues (Fuse et al, 1990;Hersh 1981;Irazusta et al, 2002). However, the studies did not include the ovary and placenta for the assay and one report indicated that the ovary contained higher POP activity than the brain in the mouse (Ohta et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…The POP enzymatic activity or its mRNA expression have been reported to be high at early developmental stages of the rat brain (Kato et al, 1980;Fuse et al, 1990;Yamanaka et al, 1999;Agirregoitia et al, 2003Agirregoitia et al, , 2010, pituitary (Agirregoitia et al, 2003), and liver (Matsubara et al, 1998) as well as of the mouse testis (Kimura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Prep cleaves the peptide bond at the C-terminal side of an internal proline (-Pro-Xaa, where Xaa is any amino acid other than proline) of short 30-mer peptides. Peptides larger than this size do not gain access to the active site of the enzyme and are spared from proteolysis.…”
Section: Discussionmentioning
confidence: 99%